PsycEXTRA Dataset 2005
DOI: 10.1037/e650722007-001
|View full text |Cite
|
Sign up to set email alerts
|

Tackling Domestic Violence: Effective Interventions and Approaches

Abstract: RDS is also part of National Statistics (NS). One of the aims of NS is to inform Parliament and the citizen about the state of the nation and provide a window on the work and perf o rm a n c e of government, allowing the impact of government policies and actions to be assessed.T h e re f o reResearch Development and Statistics Directorate exists to improve policy making, decision taking and practice in support of the Home Office purpose and aims, to provide the public and Parliament with information necessary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
106
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(123 citation statements)
references
References 22 publications
2
106
0
2
Order By: Relevance
“…As noted above, for those young people in secondary schools and young people's services the topic of domestic abuse was directly addressed, although over time there appears to have been a move to shift the focus to abuse in young people's own relationships 90,92,93 rather than domestic abuse in their parents' relationships. 81,88,94 This shift may reflect the impact of Barter et al's study, 4 which provided evidence on the prevalence of domestic abuse in young people's relationships in the UK. Work in primary schools was focused less on domestic abuse and more on wider relationship issues such as friendship, respect and children's safety.…”
Section: Programme Contentmentioning
confidence: 99%
See 4 more Smart Citations
“…As noted above, for those young people in secondary schools and young people's services the topic of domestic abuse was directly addressed, although over time there appears to have been a move to shift the focus to abuse in young people's own relationships 90,92,93 rather than domestic abuse in their parents' relationships. 81,88,94 This shift may reflect the impact of Barter et al's study, 4 which provided evidence on the prevalence of domestic abuse in young people's relationships in the UK. Work in primary schools was focused less on domestic abuse and more on wider relationship issues such as friendship, respect and children's safety.…”
Section: Programme Contentmentioning
confidence: 99%
“…Fourteen studies reported on outcomes for children and young people 38,[78][79][80][81][82][83][84]88,94 and nine reported programme participants' satisfaction with data gathered predominantly through pre and post questionnaires and focus groups. 38,[78][79][80][81][82][83]85,88 Three were specifically process evaluations.…”
Section: Summary Of Chapter 4 Findingsmentioning
confidence: 99%
See 3 more Smart Citations